Peran Kantor Urusan Agama (KUA) Kecamatan Siman dalam Pembentukan Keluarga Sakinah Perspektif Undang-Undang Nomor 11 Tahun 2009 Studi Kasus Di Desa Ngabar Kecamatan Siman Kabupaten Ponorogo - Sari, Hazi Kurniva (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2021)
Muslims believe that marriage is the best way to have children and maintain self-respect. In the Compilation of Islamic Law Article 3 paragraph (1) it is explained: the purpose of marriage is to realize a sakinah, mawaddah, warohmah household life. There are many ways to form a family, but the people of Ngabar Village, Siman District, Ponorogo Regency, and also other people do not know how to form a harmonious family. This study aims to (1) determine the understanding of the Ngabar Village community towards Law Number 11 of 2009 concerning Social Welfare, (2) to determine the role of KUA Siman District in the formation of a sakinah family in Ngabar Village, Siman District, Ponorogo Regency. This type of research is Field Research. A descriptive approach is used in this study. The results of this study indicate: The people of Ngabar Village do not understand the meaning of social welfare even though the employees of the Siman District Religious Affairs Office have socialized Law Number 11 of 2009 concerning social welfare. As a result, the formation of a sakinah family in Ngabar Village has not been carried out as much as expected.